'BLINDNESS CURED!': RESPONSE TO LATE STEROIDS IN CRION. (29th November 2012) - Wong, S; Cleary, G; Graham, EM; Plant, GT
Abstract : A 50-year-old man presented with a 7 year history of visual loss. He was medically retired as a doctor. His right eye was amblyopic. Initial loss was subacute, bilateral and painful, following which the pain improved but there was ongoing gradual visual decline, interspersed by two stepwise painful worsenings at 6 months and 2 years. Pain on eye movements continued. At initial presentation he had cupped optic discs and high-normal intraocular pressures; glaucoma treatment was started. Acuity then was 6/9 (left eye), 6/60 (right eye). Neurological assessment and CSF examination were normal. MRI (2005) was reported locally to show right optic nerve intrinsic signal change only. He continued under care of Ophthalmology; last reviewed by Neurology in 2005. He was registered blind in 2007, when his vision reached the level of counting fingers only. In 2011 his literature search led to a short course of steroids. He reported transient improvement and arranged a referral to our unit. We started high-dose prednisolone. After 2 weeks, his vision improved from counting fingers to 6/6 (left) and 6/60 (right). We report a patient with Chronic Relapsing Inflammatory Optic Neuropathy, who demonstrates a dramatic response to late use of steroids. We conclude that if a non-MS type of optic neuritis is suspected, corticosteroid treatment should be considered in both acute and chronic cases.